Doctors Need Different Doctors to Treat Their Relatives: A Subject That Does Not Receive Enough Attention in Medical Education - Nazan Kaymaz; Şule Yıldırım; Fatih Battal; Hakan Aylanç (Trends in Pediatrics)
Due to having medical knowledge, sometimes doctors may not need to refer to other doctors in case of illness of themselves or their relatives. Therefore, the correct diagnosis may be delayed. This paper discussed this issue from the perspective of a daughter whose father, a doctor, caused the diagnosis of her diseases to be delayed. However, delay in diagnosis is difficult to measure, reasons for the delay can originate from the system or can be caused by the course of the disease, by the patient, and sometimes by physicians, as in our patient.